Studies on determining favourable factors for the germination of conidia of Oidium mangiferae - A. VARMA, P. SINHA , PRAJNESHU and (Indian Phytopathology, 2002)
The powdery mildew caused by Oidium mangiferae Berthet produces huge number of air-borne conidia which germinate under the influence of temperature and relative humidity. To find out their optimum values, studies have been carried out on the laboratory observations of conidia germination and germ tube growth. The optimum values for temperature corresponding to maximum rate for germination and germ tube growth are of great relevance from the epidemiologicalstandpoint. On the basis of models fitted, it is concluded that optimum temperatures for conidia germination and germ tube growth are about 2S.1-28.2°Cand 22.9°C respectively, while the corresponding optimum interval estimatesfor the top 10% are about 22.8-31.8°C and 18.4-27.rC respectively. Further, empirical considerations indicate that the optimum relative humidity level and the incubation period for both conidia germination and germ tube growth are about 80% and 48 hours respectively.